Antibiotics from Carbon Dioxide: Sustainable Pathways to Pharmaceutically Relevant Cyclic Carbamates. Issue 6 (12th December 2018) - Niemi, Teemu; Repo, Timo
Abstract : As a versatile and sustainable C1 source, carbon dioxide can substitute toxic reagents such as isocyanates and phosgene in many organic syntheses. In particular, it readily couples with amines to give various carbamate species. This reactivity can be exploited in the synthesis of cyclic carbamates, which are structural motifs found in many antibiotics and other pharmaceutically relevant or otherwise high value‐added compounds. In this Minireview, we explore the four major categories of carbon dioxide‐based syntheses of cyclic carbamates: cycloaddition of CO2 into aziridines, epoxide‐based methods, cyclization of unsaturated compounds, and cyclization of amino alcohols. Abstract : Cyclic carbamates are core structures found in many pharmaceuticals. Their synthesis usually involves phosgene or other toxic and expensive reagents, which should be replaced with greener and equally efficient carbon dioxide‐based methods. This Minireview summarizes the major pathways from CO2 to cyclic carbamates and recent developments on the topic.